Product assurance for instrumental projects in research laboratory: galaxies, etoiles, physique, instrumentation (GEPI) - De Frondat, F; Jagourel, P; Frotin, M; Hammer, F; Rodrigues, M; Puech, M; Guinouard, I; Chemla, F; Yang, Y; Fitzsimons, E; Parr-Burman, P; Morris, T; et al. (Society of Photo-optical Instrumentation Engineers, 2018)
Product Assurance is an essential activity to support the design and construction of complex instruments developed for major scientific programs. The international size of current consortia in astrophysics, the ambitious and challenging developments, make the product assurance issues very important. The objective of this paper is to focus in particular on the application of Product Assurance Activities to a project such as MOSAIC, within an international consortium. The paper will also give a general overview on main product assurance tasks to be implemented during the development from the design study to the validation of the manufacturing, assembly, integration and test (MAIT) process and the delivery of the instrument.